Double jeopardy: Examining the burden and bias faced by new mothers working in Indian educational institutions - Dr. Rati Khurana,; Dr. Aanchal Chaudhary, (The Bioscan, 2025)
In the Indian culture, women are usually expected to take up the role of a caregiver for their newborns while compromising on their other roles. Moreover, mothers employed in Indian educational institutions tend to experience dual burden of providing care to their neonates while facing systemic gender bias leading to “double jeopardy” negatively impacting their career in the academia. This qualitative study, based out of Delhi NCR, explores the lived experiences of ten new mothers with children aged 0-2 years who are employed as teachers, lecturers or professors at any Indian educational institutions navigating the challenges of balancing motherhood while maintaining a positive professional trajectory. Using in-depth interviews, the research identifies key themes, including institutional barriers, implicit and explicit biases, and the socio-cultural expectations that exacerbate their struggles. Findings indicate that new mothers often face limited structural support, discriminatory policies, and a lack of accommodation for their dual roles. The study presents crucial topics for discussion such as gender based biasness/discrimination in academia by highlighting the urgent need for policy reforms, inclusive workspaces, and institutional sensitivity to the unique challenges faced by new mothers working in Indian educational institutions. The implications extend to fostering gender equity, ensuring work-life balance, and promoting systemic changes within academic institutions to support women employed in academia.